2022
DOI: 10.11591/ijpeds.v13.i1.pp390-400
|View full text |Cite
|
Sign up to set email alerts
|

Novel multi-device unified powerquality conditioner for powerquality improvement

Abstract: This paper describes the customizable multi-device unified power-quality conditioner (MD-UPQC) is designed especially for multi-feeder distribution networks. The proposed MD-UPQC can exchange the power between the multi-feeders and proficiently mitigates all voltage-current associated power-quality problems, make sure to maintain balanced power-flow to consumers. At recent days, various manufacturers recommend the provision of multilevel inverters in mid-range customized compensation devices with desirable con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…It generates reference signals by detecting the load voltage value and generating unified vector values in a pre-synchronized angle (s) using a discrete phase-locked loop (DPLL). The authors present the mathematical modeling and design of the suggested UVCR control method in [27]. The measured values and the derived reference current-voltage signals from the UVCR control scheme are propagated using the RCB-PWM approach.…”
Section: Proposed 5-level Reduced-switch Multilevel Inverter Topologymentioning
confidence: 99%
See 2 more Smart Citations
“…It generates reference signals by detecting the load voltage value and generating unified vector values in a pre-synchronized angle (s) using a discrete phase-locked loop (DPLL). The authors present the mathematical modeling and design of the suggested UVCR control method in [27]. The measured values and the derived reference current-voltage signals from the UVCR control scheme are propagated using the RCB-PWM approach.…”
Section: Proposed 5-level Reduced-switch Multilevel Inverter Topologymentioning
confidence: 99%
“…The working and performance of the proposed UVCRcontrolled RSMLI-MDUPQC device under various PQ signatures have been evaluated through the MATLAB/Simulink software tool and simulation results are illustrated. The system specifications and the values are stated in [27] and depicted in…”
Section: Proposed 5-level Reduced-switch Multilevel Inverter Topologymentioning
confidence: 99%
See 1 more Smart Citation
“…By using this CPC technology, various custom-power devices have been designed for compensation of associated voltage-current PQ problems to formulate the PCC of electric-grid as balanced, sinusoidal shape, fundamental nature as per IEC/IEEE standards [11]- [13]. The classification of CPC devices has been selected based on distinct PQ concerns which including, active power filters (APF's) [14], dynamic voltage regulators (DVR's) [15], distributed static compensators (DSTATCOM's) [16] and universal power-quality conditioners (UPQC) [17]- [19]. Among the aforementioned CPC devices, the AUPQC's has been specifically developing for power distribution system is explored in [20].…”
Section: Introductionmentioning
confidence: 99%
“…The authors offer a three-phase CHB inverter with a third harmonic correction mechanism (THCS). Then, for single phase CHB inverters, a THCS methodology is developed that effectively overcomes the shortcomings of the previous techniques [4], [5]. That is, it ensures that the system can function with a unit power factor and a reasonably small change in DC-link voltage while without reducing power output.…”
Section: Introductionmentioning
confidence: 99%